Thank you for the opportunity to help you with your question!
Your equation is: f(x) = 1 + 3xSolve for x. Subtract 1 to both sides of this equation to get: f(x) -1 = 3x Divide both sides of this equation by 7 to get: (f(x) -1)/3 = x Since, in general, a = b implies that b = a, this equation becomes: x = (f(x) -1)/3Replace x with f(x) and replace f(x) with x to get: f(x) = (x-1)/3That's your inverse function.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?